Investigation of plasma lenses in NSC KIPT - Onishchenko, I.N. (Вопросы атомной науки и техники, 2012)
The results of carried out at NSC KIPT theoretical and experimental studies of focusing electron and ion beams with using plasma lens are presented. Several mechanisms of beam focusing in plasma are considered: plasma compensation of defocusing space charge field of the beam, focusing by electric and magnetic fields of charged current-carrying plasma, ejected from the plasma gun, and focusing by high-frequency wakefield excited in plasma by a sequence of short relativistic electron bunches.